Bringing Institutions into Economics when Teaching Economics as a Minor Subject - Martin Kniepert (Universität für Bodenkultur Wien, Department für Wirtschafts- und Sozialwissenschaften, Institut für nachhaltige Wirtschaftsentwicklung, 2017)
Developments in economic policy since the 1980s have shown a general trend towards a single type of institutional arrangement, following short-term, immediately applicable efficiency criteria. This was supported through the teaching by putting particular weight on the corresponding analytical instruments. The thesis presented here observes a systematic bias in this. It does so by evaluating institutional trends in the various sectors of the economy, and by discussing institutional arrangements of selected areas in detail. Furthermore, it reviews contributions by representatives of New Institutional Economics for a more comprehensive approach. Based on this, institutions themselves are conceptualised as public or club goods. As such they are applied to the policy areas selected. It can thereby be shown that microeconomic theory can find an appropriate place in this extended economic approach, along with concepts like common-pool resource management. In conclusion, this thesis proposes giving considerably more space to institutions in economics curricula, to their evolution and implications for economic outcomes. Particularly for economics as a minor subject, more emphasis should be placed on institutional arrangements.
Keywords: B25; B20; N54; A22; 330; New Institutional Economics; History of Economic Thought; Agricultural Economics; Teaching of Economics